On the algebraic structure of isotropic generalized elasticity theories. (May 2015) - Auffray, N
In this paper the algebraic structure of the isotropic n th-order gradient elasticity is investigated. In the classical isotropic elasticity it is well known that the constitutive relation can be broken down into two uncoupled relations between the elementary part of the strain and the stress tensors (deviatoric and spherical). In this paper we demonstrate that this result can not be generalized because in 2nd-order isotropic elasticity there exist couplings between elementary parts of higher-order strain and stress tensors. Therefore, and in certain way, n th-order isotropic elasticity have the same kind of algebraic structure as anisotropic classical elasticity. This structure is investigated in the case of 2nd-order isotropic elasticity, and moduli characterizing the behavior are provided.